Effects of dietary conjugated linoleic acid (CLA), n-3 and n-6 fatty acids on performance and carcass traits of broiler chickens - Royan, Maryam; Goh, Yong Meng; Othman, Fauziah; Sazili, Awis Qurni; Navidshad, Bahman (Academic Journals, 2011)
An experiment was conducted on broiler chickens to study the effects of conjugated linoleic acid (CLA), fish oil, soybean oil or their mixtures (at 7% for single and 3.5% + 3.5% for mixtures) as well as up 12% dosage of palm oil, on the performance and carcass traits of broiler chickens. The chicks fed 7% fish oil or 7% CLA diets were found to have the most inferior weight gain in grower and finisher phases, respectively. A significant reduction in feed intake was observed with diets containing 7% fish oil. However, adding CLA to the diets regardless of the associated dietary fat, did not affect birds feed intake. The dietary fish oil and CLA adversely affected the feed conversion ratio as well as carcass yield. Dietary palm oil (at 12% level) and CLA (at 7% level) increased the abdominal fat pad and liver weights, respectively. The results of this study show that the high dosage of fish oil or CLA can reduce broiler chickens performance but their combination with soybean oil as n-6 fatty acid source can moderate these adverse effects.